Hakim Sebagai Penegak Etika Profesi Hukum: Suatu Kajian Tentang Independensi Dan Integritas - Pramudita Antasia; Kayus Kayowuan Lewoleba (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Ethics is a value that must be understood and owned by everyone, with ethics, life together can be arranged as we expect. However, in practice, law enforcement in Indonesia still finds problems that distance the law from its main goal of providing justice, certainty, and benefits for the community. This study raises issues related to the relationship between judicial independence and integrity with the enforcement of legal professional ethics, as well as factors that can affect the independence and integrity of the judiciary in court processes. The methods used in this study are normative juridical and literature research, both of which are secondary data collection methods. Then, it can be concluded that judges who uphold the independence and integrity of their judiciary, can show the meaning of legal professional ethics. The relationship between the independence and integrity of the judiciary and the ethics of the legal profession is very close, because independence and integrity are the main conditions for the realization of the rule of law, and are guarantees for the upholding of law and justice.